Impact of Efficiency of Intermediation Functions from Financial Institutions on Consumer Surplus on The Balance of The Fund Market in Indonesia - Rejekiningsih, Tri Wahyu; Atmanti, Hastarini Dwi (AKSIOMA : Jurnal Sains Ekonomi dan Edukasi, 2025)
The greater the amount of savings than the loan amount in banking shows that problems on non-performing loan (NPL). The objectives of this study was: to analyze the efficiency of the intermediation function of financial institutions (banking), and the impact of efficiency of financial institution intermediation function to consumer surplus in the fund market. Partial Adjustment Model (PAM) were used to analyze efficiency and consumer surplus using panel data 2000 – 2016. The result showed that the efficiency of the financial institution intermediary function influenced the size of the consumer surplus in the fund market. Therefore, that consumer surplus in the fund market was influenced by the performance of financial institutions. This consumer surplus is of the lack of fund group (deficit unit) due to equilibrium change in fund market. To anticipate future funding needs, it is necessary to conduct a study of the consumer surplus of funds based on the type of use of financial lending in financial institutions in the economy.